REDUCTION OF LEAKAGE FROM ORGANIC MANURE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Environmental problems of leakage minimisation from solid manure handling in Latvia are discussed. Volume and composition of leakage from solid manure are investigated in storage period. Amount of plant nutrients in effluents are measured 0,099 kg nitrogen, 0,029 kg phosphorus and 0,381 kg potassium per tonne manure in 14-day period of accumulation and storage of solid manure in trailer. Plant nutrients losses in effluent from densely stockpiled manure are 0,40 kg nitrogen, 0,197 kg phosphorus and 1,372 kg potassium per tonne manure in 5— moth storage period while leakage were occurred. In first 2— month period nutrient losses are 74 % nitrogen, 54 % phosphorus and 54 % potassium of whole amount of losses in 5-month period. Proposed recommendations are aimed to minimise the leakage from solid manure in farms in Latvia.